Monitoring methodologies and tools for the Sustainable Energy Action Plans to support the Public Administration. (August 2018) - Cinocca, Andrea; Santini, Fabrizio; Cipollone, Roberto
Abstract: Climate Change invites to a more comprehensive analysis that regards Sustainable Development. Many expertises are involved in this aim, also extending the area of interest toward interdisciplinary aspects not only related to engineering aspects. Sustainable Development gives more responsibility to local administrations, following the key principle of "glocalization", (thinking globally, acting locally): Municipalities are the smallest political responsible nucleus called to act and to put in place planning actions which answers to big questions (energy demand, climate change, etc.) which worry the common future of Humanity. Sustainable Energy Action Plans are the voluntary operational tools conceived by the European Union for the implementation of community energy policies. Province of L'Aquila (in the Abruzzo Region, Italy) has been a leading player of this program and has realized the ambitious goal of having signed the Covenant joining all the 108 Municipalities of the Province. Department of Industrial and Information Engineering and Economics (DIIIE) of the University of L'Aquila designed the SEAPs and the monitoring phase of all the Municipalities through a scientific methodology which is reported in this paper.